MENINGKATKAN INTELEGENSI PETANI MENGENAI PUPUK ALTERNATIF DENGAN PUPUK ORGANIK PHOTOSYNTHETIC BACTERIA (PSB) DI DESA BIRU - Mochamad Ramdan¹*, Fajri Shiddiq2*, Hudan Luqmanul Hakim2,M. Ilham Putra Setiawan2, Sabila Medina Se (Jurnal Pengabdian Kepada Masyarakat Agri Hatantiring, 2024)
PSB (Photosynthetic Bacteria) fertilizer is an alternative fertilizer made from a variety of materials that are easily found in everyday life, with the skyrocketing prices of subsidized fertilizers PSB fertilizer is expected to be an alternative to the needs of the community to save budget. Not only about saving the budget, another advantage when using PSB fertilizer is that it makes plants get the nutrients they need and makes plants carry out photosynthesis by utilizing sunlight to the maximum. the results will also be better than plants that do not use PSB fertilizer, both in size, taste, and quality. Before introducing this fertilizer, a questionnaire was held to find out how high the knowledge of farmers about fertilizers, and the results were that farmers only knew organic fertilizers or fertilizers in general, therefore PSB fertilizer was introduced as the answer to the problems experienced by farmers starting from socialization, introducing PSB fertilizer itself, explaining the ingredients needed and their benefits, to direct practice with farmers. This aims to make farmers less dependent on subsidized fertilizers and make them more familiar with alternative fertilizers.